Comparison of the effects of two sprinkler systems on populations of vanda orchid scale - McConnell, J. (2013)
Impact and spinner sprinklers were evaluated for their ability to suppress the populations of vanda orchid scale. Sixty plants of Vanda x Miss Joaquim infested with vanda orchid scale, Genaparlatoria pseudaspidiotus (Lindinger) were divided into two equal plots and were established under each kind of sprinkler. Impact sprinklers did not reduce scale populations. A marked reduction in the scale population was found both on the leaves and on the stems of vandas irrigated with spinner sprinklers in a six-month period. No further reduction was observed between the six and eight months samples. This study indicates that by selecting spinner sprinklers for irrigation there is the added benefit of controlling scale and reducing the insecticide usage.